Measurement of angular parameters from the decay B0 → K⁎0μ+μ− in proton–proton collisions at s=8TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Elsevier BV, 2018)
Angular distributions of the decay B0 → K∗0μ+μ− are studied using a sample of proton–proton collisions at √s = 8 TeV collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 20.5 fb−1. An angular analysis is performed to determine the P1 and P 5 parameters, where the P 5 parameter is of particular interest because of recent measurements that indicate a potential discrepancy with the standard model predictions. Based on a sample of 1397 signal events, the P1 and P 5 parameters are determined as a function of the dimuon invariant mass squared. The measurements are in agreement with predictions based on the standard model